Analysis of the Effectiveness of Differentiated Learning in Implementing an Independent Curriculum on Student Learning Outcomes in Lima Puluh Kota Indonesia - Marlina, Eli; Muharja, Fajri (MANAZHIM, 2024)
This research aims to see the effectiveness of differentiated learning in implementing the independent curriculum on the learning outcomes of state high school students in Limapuluh Kota Regency. The research was conducted at the Limapuluh Kota District High School with research data sources from basic educational data from SMA 1 and SMA 2 Harau, as well as data from the Central Statistics Agency (BPS) and the Limapuluh Kota Regency Education Office. This research uses Ordinary Least Squares (OLS) multiple linear regression data analysis techniques. The results of the research show that the implementation of learning styles has not significantly influenced learning outcomes, but other X variables, namely teacher competence, school environment, and student personality (IQ and gender), have an influence on student learning outcomes. Meanwhile, students' sociodemographic factors do not influence learning outcomes in certain subjects. The competency of driving teachers influences mathematics learning outcomes and Indonesian language learning outcomes. Apart from that, the boarding school environment also influences student learning outcomes in Indonesian language subjects, economic subjects, and arts and culture subjects. Student personal factors related to the IQ variable also influence student learning outcomes, with a difference in scores of 0.22 in mathematics subjects and 0.18 in economics subjects. Meanwhile, the gender variable influences economic learning outcomes with a score difference of 58.62, where female students have a higher score of 58.62 than male students.